The role of meso-institutions in the system of tariff regulation of energy and housing and public utilities markets - N. V. Popov (Вестник университета)
This article is aimed at expanding the applicability of meso-institutional concept in the markets of natural monopolies in the context of a new institutional economic theory. Within the framework of the considered concept the impact of the institutional environment level on evolutionary development of energy and housing and public utilities markets is evaluated alongside with modern approaches of digitalisation. In the first part of the current article the author describes theoretical foundations of the meso-institutional environment concept in respect to the energy and housing and public utilities markets. The definition of the concept and its usage domain are given. Besides, the goals difference of meso- and macro-institutions are analysed in detail. The theoretical part also covers approaches of A.E. Shastitko applied to the energy and housing and public utilities markets. Moreover, the hypothesis of conflict resolution between macro- and meso-institutions is described in framework of markets regulation mechanisms. Also, the regulation mechanisms of the two markets are analysed, including market power instruments of meso-institutions. In addition, the article covers the problem of maintaining a balance of market participants’ interests through these mechanisms. In conclusion, the author offers the concept of improving market mechanisms with the help of the meso-institutional development strategy. It is designed to solve the problem of maintaining a balance of market participants’ interests and predetermine the formation of a new improved institutional environment in the energy and housing and public utilities markets.